Hopes and prospects - Chomsky, Noam (Chicago : Haymarket Books, 2010)
Chomsky shows how direct participation in action in the United States, Latin America, Bolivia, and Haiti in particular has put into practice a different model of democracy that could portend more far-reaching, badly needed changes.
Argues that direct participation in action in the United States, Latin America, Bolivia, and Haiti has put into practice a different model of democracy that could portend more far-reaching, badly needed changes.
Latin America. Year 514 : globalization for whom? -- Latin America and U.S. foreign policy -- Democracy and development : their enemies, their hopes -- Latin American and Caribbean unity -- North America. "Good news," Iraq and beyond -- Free elections, good news and bad -- Century's challenges -- Turning point? -- Elections 2008 : hope confronts the real world -- Obama on Israel-Palestine -- The torture memos -- 1989 and beyond.
Includes bibliographical references (p. 281-313) and index.
Keywords: World politics -- 21st century; Latin American federation; Arab-Israeli conflict -- 1993-; World politics -- 1991-; Israel-Arab conflicts; United States -- Foreign relations -- 21st century; United States -- Politics and government -- 2009-; United States -- Foreign relations -- Latin America; Latin America -- Foreign relations -- United States; United States -- Foreign relations; United States -- Politics and government; United States -- Foreign relations -- Latin America; Latin America -- Foreign relations -- United States